Multi-scale magnetic mapping of serpentinite carbonation. Issue 1 (December 2017) - Tominaga, Masako; Beinlich, Andreas; Lima, Eduardo; Tivey, Maurice; Hampton, Brian; Weiss, Benjamin; Harigane, Yumiko
Abstract Peridotite carbonation represents a critical step within the long-term carbon cycle by sequestering volatile CO2 in solid carbonate. This has been proposed as one potential pathway to mitigate the effects of greenhouse gas release. Most of our current understanding of reaction mechanisms is based on hand specimen and laboratory-scale analyses. Linking laboratory-scale observations to field scale processes remains challenging. Here we present the first geophysical characterization of serpentinite carbonation across scales ranging from km to sub-mm by combining aeromagnetic observations, outcrop- and thin section-scale magnetic mapping. At all scales, magnetic anomalies coherently change across reaction fronts separating assemblages indicative of incipient, intermittent, and final reaction progress. The abundance of magnetic minerals correlates with reaction progress, causing amplitude and wavelength variations in associated magnetic anomalies. This correlation represents a foundation for characterizing the extent and degree of in situ ultramafic rock carbonation in space and time. Peridotite carbonation plays an important role in the carbon cycle. Here, the authors present a geophysical characterization of serpentinite carbonation from km to mm scale and confirm that the abundance of magnetic minerals provides a strong correlation with the overall carbonation reaction process.